BANG ONIM'S DIGITAL POETRY MODEL AS AN INFLUENCER AND HUMANIST ACTIVISTS IN PALESTINE - Dewi Anggrayni; Shabrina Khairani; Rosmawati Binti Mohammad Rasit; Atikah Dewi Utami (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2024)
Social media has a significant influence on various aspects of life, including in humanitarian social action activities. The Palestinian care action carried out by influencers has utilized social media as a means of social interaction. Not a few social communities have made an invitation to donate to care for Palestine, boycott Israel or other humanitarian actions as a form of support for Palestine by gathering the attention of their followers on social media. However, not all influencers have optimized digital space specifically for calls for goodness like da'wah content. This study aims to see how the @bangonim account displays its experiences in humanitarian action in Palestine. Using a descriptive qualitative methodology, researchers analyzed the content of @bangonim posts for the period October - December 2023 which tell of its role in various humanitarian actions in Palestine. Researchers focused on the moral and worship content displayed by @bangonim in its posts in the form of an invitation to care for Palestine. For moral posts, researchers found two main themes, namely caring for orphans and honoring elders. The two themes of the posts displayed convey the importance of providing moral and material support to children and parents in Palestine who have lost their families with humanitarian assistance. On the theme of worship, researchers found 3 contents of posts displayed by @bangonim, namely giving alms, maintaining prayer and loving the Qur'an. In this worship theme post, @bangonim tries to invite followers that it is included in worship activities when a Muslim cares about the condition of Palestine. As a humanitarian influencer, @bangonim tries to convey an invitation to goodness by including existing facts and realities, accompanied by examples of his social activities as a form of real humanitarian support. Through posting reels content and posters of humanitarian action to defend Palestine, he succeeded in realizing social change in the perspective of da'wah bil hikmah through social media. Keywords: Social Media, Windows on Events and experiences, Humanitarian Action, Instagram Posts